Mitochondrial neurogastrointestinal encephalomyopathy imitating Crohn's disease: a rare cause of malnutrition - Kučerová, Lenka; Dolina, Jiří; Dastych, Milan; Bartušek, Daniel; Honzík, Tomáš; Mazanec, Jan; Kunovský, Lumír (Journal of gastrointestinal and liver diseases, 2018)
Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is a rare autosomal recessive disease caused by a mutation in the TYMP gene encoding thymidine phosphorylase. MNGIE causes gastrointestinal and neurological symptoms in homozygous individuals and is often misdiagnosed as anorexia nervosa, inflammatory bowel disease, or celiac disease. We present the case of a 26-year-old female with MNGIE, who was initially diagnosed with anorexia nervosa and Crohn's disease. The diagnosis of MNGIE was established by biochemical confirmation of elevated serum and urine thymidine and deoxyuridine levels after multiple examinations and several years of disease progression and ineffective treatment. Subsequent molecular genetic testing demonstrated a homozygous TYMP gene mutation. MNGIE should be considered in patients with unexplained malnutrition, intestinal dysmotility, and atypical neurological symptoms.
Keywords: Mutation; Intestinal Pseudo-Obstruction; Nutritional Status; Crohnova nemoc; Biopsy; Humans; lidé; thymidinfosforylasa; magnetická rezonanční tomografie; prediktivní hodnota testů; svalová dystrofie okulofaryngeální; Anorexia Nervosa; nutriční stav; Treatment Outcome; Magnetic Resonance Imaging; počítačová rentgenová tomografie; Tomography, X-Ray Computed; Predictive Value of Tests; Malnutrition; Thymidine Phosphorylase; Female; Diagnosis, Differential; hodnocení stavu výživy; Adult; mutace; DNA Mutational Analysis; výsledek terapie; parenterální výživa; Phenotype; Nutrition Assessment; mutační analýza DNA; Muscular Dystrophy, Oculopharyngeal; podvýživa; ženské pohlaví; fenotyp; Parenteral Nutrition; Genetic Predisposition to Disease; dospělí; střevní pseudoobstrukce; Crohn Disease; genetická predispozice k nemoci; diferenciální diagnóza; mentální anorexie; biopsie